2013
DOI: 10.1097/pgp.0b013e31826a642b
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 Expression and Prognostic Significance in Ovarian Carcinoma

Abstract: The transcription factor SOX2 has been extensively studied for its role in embryonic stem cell self-renewal and pluripotency. More recent data suggest oncogenic functions of SOX2 and demonstrate expression in several carcinoma types, predominantly of squamous cell origin. The gene SOX2 is located at chromosome 3q26, a region that is frequently amplified in ovarian high-grade serous carcinoma. In this study, we correlate SOX2 protein expression and gene-amplification status in ovarian carcinomas with histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 6 publications
4
25
0
Order By: Relevance
“…In SOC, high SOX2 protein expression is associated with histopathologically and clinically aggressive disease (18,19,46). Similar as in breast carcinoma (13), we found that SOX2 þ expressing ovarian carcinomas display a heterogeneous expression pattern with mostly less than 10% of tumor cells expressing SOX2 protein, indicating that SOX2 might preferentially regulate the ovarian CSC compartment.…”
Section: Discussionsupporting
confidence: 82%
“…In SOC, high SOX2 protein expression is associated with histopathologically and clinically aggressive disease (18,19,46). Similar as in breast carcinoma (13), we found that SOX2 þ expressing ovarian carcinomas display a heterogeneous expression pattern with mostly less than 10% of tumor cells expressing SOX2 protein, indicating that SOX2 might preferentially regulate the ovarian CSC compartment.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the slides were counterstained with hematoxylin, dehydrated, cleared and then mounted with Permount mounting medium (Fisher Scientific, PA). TRPM7 staining was scored independently by two pathologists and was calculated using a previously defined scoring system (Pham et al, 2013;Qiu et al, 2013). Briefly, the proportion of positive tumor cell was scored as: 0 = less than 5%; 1+ =5%-20 %; 2+ = 21%-50 %; and 3+ > 50 %.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…SOX2 has been found in brain, breast, lung, liver, prostate, and testicular tumors [12, 18, 19]; and its expression has been correlated with poor prognosis in stage I lung adenocarcinoma [18], squamous cell carcinoma [20, 21], gastric carcinoma [22-24], small cell lung cancer [25-28], and ovarian carcinoma [29, 30]. …”
Section: Introductionmentioning
confidence: 99%